Digital Media Interventions for Anemia Prevention Among Adolescent Girls: A Scoping Review - Annisa Aulia Fitri; Mohammad Zen Rahfiludin; Farid Agushybana (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Anemia among adolescent girls remains a global health concern, with prevalence reaching 30.7% among women aged 15–49 years in 2023. Education is essential in shaping behaviors toward anemia prevention. The rapid expansion of digital platforms provides new opportunities to deliver engaging and accessible health education. This review aimed to map available evidence on digital media interventions designed to improve anemia-related behaviors among adolescent girls. Methods: This review followed PRISMA guidelines. Eligible studies were interventional in design (quasi-experimental or pre–post), evaluated digital media interventions (e.g., videos, animations, social media, mobile applications, websites, or e-leaflets), targeted adolescent girls aged 12–22 years, and reported at least one behavioral outcome related to anemia. Studies published between 2014 and 2024 in English or Indonesian full text were included. Exclusion criteria comprised studies published before 2014, non-original research, studies not specific to anemia or adolescent girls, interventions not involving digital media, inaccessible paid articles, and ineligible designs. Searches were conducted in Scopus, ScienceDirect, and PubMed, and completed on 24 December 2024. Screening and extraction were managed using Mendeley and followed the PRISMA stages. Data were extracted on study characteristics, intervention details, comparator groups (where available), outcomes, and findings. Results: Nine studies fulfilled the criteria. Most reported significant improvements in knowledge, while some also showed gains in attitudes and practices. The most frequently used interventions included animated videos, mobile applications, and social media platforms, with interactive and visually engaging formats yielding stronger effects. Conclusion: Digital media interventions have demonstrated effectiveness in improving anemia-related behaviors among adolescent girls, with consistent effects observed in knowledge. Integration of these approaches into adolescent health programs is recommended. However, further rigorous research comparing different digital modalities is needed to guide implementation in diverse settings.